Secondary Flows in Straight Non-Circular Tubes - Giesekus Fluid - Letelier-Sotomayor, M; Stockle-Henriquez, J; Siginer, D (American Society of Mechanical Engineers, 2013)
Flow of Giesekus fluids in straight, arbitrary but axiallysymmetric non-circular tubes is investigated. The crosssectional shapes are obtained through a one-to-one continuous mapping of the circular base contour. The primary longitudinal and the secondary fields are elucidated up to and including the third order in the Weissenberg number Wi. Copyright © 2013 by ASME.